Type II Top-Leone generalized Lomax distribution and application to hydrological data - Fatoki‡, O.; Adeleye*, N.F.; Omosigho, D.O. (International Journal of Mathematical Analysis and Modelling, 2023)
In this paper, a new three-parameter extended Lomax distribution called the Type II Top-Leone Lomax distribution was developed. We demonstrated its flexibility and tractability over inverse Lomax distribution through various theoretical and practical approaches. The derived properties include the quantiles, moments, Renyi entropy, and order statistics. Finally, we consider a river data set to demonstrate the flexibility of the newly developed model.